Relationship of BMI and Parity with High Grade Serous Ovarian Cancer at RSUP Dr. M. Djamil Padang - Syamel Muhammad; Eka Nofita; Henny Mulyani; Selfi Renita Rusjdi; Fathiyyatul Khaira; Murizal, Thanya Amoret Alya (Fakultas Kedokteran Universitas Andalas, 2025)
Introduction : Ovarian cancer is the 8th most common cancer in women. High grade serous carcinoma (HGSC) is a subtype of ovarian cancer with the highest case and death rate compared to other types. Therefore, a preventive approach is needed by reviewing the underlying risk factors of this cancer. Body mass index (BMI) and parity are modifiable risk factors for ovarian cancer. This study aims to determine the relationship BMI and parity on high grade serous subtype ovarian cancer at RSUP Dr. M. Djamil Padang. Method: observational analytic study with a cross sectional approach. This research was conducted at RSUP Dr. M. Djamil Padang using medical record data of epithelial ovarian cancer patients at RSUP Dr. M. Djamil Padang from 2021 to 2022 with a sample of 129 patients. The data analysis method used in this research is the Chi-square test. Result : Epithelial ovarian cancer patients are most found at >50 years old (55%), menopausal woman (65.9%), non obese (77.5%) and parous women (76%). Conclusion : There was no relationship between body mass index and parity with the incidence of ovarian cancer, subtype high grade serous, at RSUP Dr. M. Djamil Padang.